Adaptive Water Distribution Networks with Dynamically Reconfigurable Topology - Wright,R; Stoianov,I; Parpas,P; Henderson,K; King,J (Journal of Hydroinformatics, 2014)
This paper presents a novel concept of adaptive water distribution networks withdynamically reconfigurable topology for optimal pressure control, leakage management and improved system resilience. The implementation of District Meter Areas (DMAs) has greatly assisted water utilities in reducing leakage. DMAs segregate water networks into small areas; the flow in and out of each area is monitored and thresholds are derived from the minimum night flow to trigger the leak localisation. A major drawback of the DMA approach is the reduced redundancy in network connectivity which has a severe impact on network resilience, incident management and water quality deterioration. The presented approach for adaptively reconfigurable networks integrates the benefits of DMAs for managing leakage with the advantages of large scale looped networks for increased redundancy in connectivity, reliability and resilience. Self-powered multi-function network controllers are designed and integrated with novel telemetry tools for high-speed time-time synchronised monitoring of the dynamic hydraulic conditions. A robust and computationally efficient optimization method based on sequential convex programming is developed and applied for the dynamic and adaptive reconfiguration of water distribution networks. An investigation is carried out using an operational network to evaluate the benefits of the proposed method for dynamically configurable water supply networks.